Construction and integration of genetic map and quantitative trait locus (QTL) mapping of yield-related traits. (3rd October 2021) - Hou, Benjun; Li, Weiguo; Gao, Xinsheng; Zhang, Xiaofei; Feng, Suping; Wu, Yaoting
ABSTRACT: This study used SSR and AFLP markers to construct the genetic linkage map of Reyan5-11×PR107 population, integrated the published genetic linkage map and utilised the integrated map to perform QTL mapping of rubber yield-related traits. A genetic map consisting of 132 molecular markers (88 SSR and 44 AFLP markers) was constructed, and a joint map consisting of 143 molecular markers (99 SSR and 44 AFLP markers), which contained 19 linkage groups covering the rubber tree genome of 1298.5 cM, each linkage group containing 2–40 Mark, the average distance between the marks is 9.08 cM. Under the conditions of LOD ≥ 2.5, it was detected 2 QTLs related to girth, 3 QTLs related to dry rubber content, and 3 QTLs related to dry rubber yield per tree, 4 QTLs related to the unit secant length dry rubber yield, 5 QTLs related to the number of conducting phloem laticifer and 4 QTLs related to the number of yellow phloem laticifer.